Porosity driven photocatalytic activity of wormhole mesoporous TiO2-xNx in direct sunlight - Sivaranjani, Kumarsrinivasan; Gopinath, Chinnakonda S. (Journal of Materials Chemistry, 2011)
Results obtained by combining four important factors simultaneously, namely, wormhole mesoporosity with low diffusion length for charge carriers, high surface area, nanoparticles with high crystallinity, and visible light absorption due to N-doping, in titania (meso-TiO2-xNx) are reported. Meso-TiO2-xNx materials have been prepared by a combustion method within 10 min and by varying urea : Ti(NO3)(4) between 1 (UT1) and 10 (UT10). All of the prepared materials have been thoroughly characterised. Nanocrystalline anatase phase with high surface area (234 m(2) g(-1)), and type-IV H-3-mesoporosity is observed with UT10. Photocatalytic rhodamine-B degradation was employed to screen for the activity of the materials, and p-anisyl alcohol oxidation to p-anisaldehyde was carried out successfully in aqueous solution under direct sunlight. High photocatalytic activity of UT10 in direct sunlight, in spite of high band gap (3.24 eV), is attributed to the better utilization of holes due to the low charge diffusion barrier associated with wormhole mesoporosity along with highly crystalline, however, nanoparticulate TiO2-xNx.